NEUROPSIKOLOGI PENDIDIKAN ISLAM: UPAYA REKONSTRUKSI METODE BELAJAR PAI MELALUI PROSES INTEGRASI POTENSI KOGNITIF DAN SPIRITUAL SISWA - Raychan Assabiq; Wantini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Islamic Religious Education (PAI) is currently facing significant challenges in developing learning methods that can comprehensively integrate the cognitive and spiritual potential of students. This research aims to reconstruct an innovative PAI learning method model through a neuropsychological approach, with a primary focus on efforts to explore and integrate cognitive and spiritual dimensions in the learning process. The method used is library research with a qualitative-interpretative approach. The research was conducted through a comprehensive analysis of primary and secondary library sources, including scientific journals, reference books, and academic publications from the last 10-15 years. Data analysis techniques used content analysis and comparative analysis, with source triangulation to ensure the validity of the findings. As for The research results indicate that Islamic Religious Education (PAI) requires a holistic approach that combines cognitive and spiritual aspects to shape individuals who are intelligent and morally-spiritually mature. Religious education not only encompasses cognitive understanding but also the processing of emotions and spiritual experiences. Innovative methods such as experiential learning and deep reflection strengthen the understanding of Islamic values. The integration of cognitive and spiritual competencies in the PAI curriculum creates a generation that applies religious teachings in daily life, preparing them to face the challenges of the times.